2020
DOI: 10.1002/mds.28282
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a Management Toolkit for Lewy Body Dementia: A Pilot Cluster‐Randomized Trial

Abstract: Background Lewy body dementia, comprising both dementia with Lewy bodies and Parkinson's disease dementia, is challenging to manage because of a complex symptom profile and lack of clear evidence‐based management guidelines. Objectives We assessed the feasibility of undertaking a cluster randomized study of the introduction of an evidence‐based management toolkit for Lewy body dementia, assessing the outcomes for patients and carers as secondary measures. Methods We randomized 23 memory/dementia, movement diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Data from 127 subjects with Lewy body dementia (77 DLB, 50 PDD) were analysed from a cluster randomized trial (Diagnosis And Management Of Neurodegenerative Dementia, 'DIAMOND-Lewy' Study; ISRCTN11083027) 20 which was performed between 2016 and 2017 in 23 memory or movement disorder services across 8 main jurisdictions (trusts) of the United Kingdom National Health Service (NHS; 4 trusts in the North East and 4 trusts in East Anglia). All patients underwent clinical assessment and were diagnosed as having probable DLB or PDD according to current consensus criteria 2,3 .…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data from 127 subjects with Lewy body dementia (77 DLB, 50 PDD) were analysed from a cluster randomized trial (Diagnosis And Management Of Neurodegenerative Dementia, 'DIAMOND-Lewy' Study; ISRCTN11083027) 20 which was performed between 2016 and 2017 in 23 memory or movement disorder services across 8 main jurisdictions (trusts) of the United Kingdom National Health Service (NHS; 4 trusts in the North East and 4 trusts in East Anglia). All patients underwent clinical assessment and were diagnosed as having probable DLB or PDD according to current consensus criteria 2,3 .…”
Section: Subjectsmentioning
confidence: 99%
“…Therefore, patients who could not be followed up after the baseline measurement (n=11) were excluded, leaving 116 participants (72 DLB, 44 PDD) for the final analysis (including 107 patients with data for all 3 timepoints, 7 patients with data at baseline and 3 months, and 2 patients with data at baseline and 6 months). Results of the trial with respect to the main intervention have recently been published 20 .…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was identified that 78% of people with Lewy body dementias received a different diagnosis initially, usually Alzheimer's disease (Galvin et al, 2010a) and although rates vary in the wider literature, it is considered that approximately 50% are receiving a different or delayed diagnosis (Freer, 2017). The Lewy body Composite Risk Score (Galvin, 2015) and the Lewy body dementia assessment toolkit have been developed to help earlier identification of the disease (O'Brien et al, 2021). This provides specific screening questions to assess whether a patient has any of the core features of the condition (Galvin, 2015;Thomas et al, 2017Thomas et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%